Simulated cystic renal lesions: Quantitative x-ray phase-contrast CT - An in vitro phantom study - Fingerle, Alexander A.; Willner, Marian; Herzen, Julia; Muenzel, Daniela; Hahn, Dieter; Rummeny, Ernst J.; Noel, Peter B.; Pfeiffer, Franz (Radiology, 2014)
Purpose: To determine if grating-based x-ray phase-contrast computed tomography (CT) can allow differentiation of simulated simple, protein-rich, hemorrhagic, and enhancing cystic renal lesions in an in vitro phantom. Materials and Methods: An in vitro phantom specifically designed to simulate simple, protein-rich, hemorrhagic, and enhancing renal cysts was scanned with an experimental grating-based phase-contrast CT setup consisting of a Talbot-Lau interferometer with a rotating anode x-ray tube and a single photon counting detector. Various combinations of serum and saline (100% and 0% to 0% and 100%), blood and saline, blood and serum (100% and 0% to 6.25% and 93.75% for both), and an iodinated contrast agent and saline (7.6-1.6 mg per milliliter of saline) were used to reproduce the chemical composition of the different types of cysts. A thickened solution of an iodinated contrast agent calibrated with a clinical multidetector CT scanner served as contrast agent-enhanced renal parenchyma (195 HU at 80 kVp, 400 mAs and 98 HU at 140 kVp, 200 mAs). Standard attenuation- and phase-contrast images were reconstructed from the raw projection data. Quantitative values for attenuation and phase contrast and image noise were determined. Contrast-to-noise ratios were calculated. Simulated lesions were assessed for visual differentiability by means of pairwise comparison of the attenuation- and phase-contrast images and both images simultaneously. Results: Attenuation-contrast imaging showed large differences in Hounsfield units with increasing concentrations of iodine (118.9 HU for 1.6 mg/mL vs 331.4 HU for 7.6 mg/mL). Values for phase-contrast imaging were substantially distinguishable for saline, serum, and blood (7.9, 23.7, and 52.8 HU, respectively). Both imaging modalities combined allowed differentiation of all four types of simulated cysts (100% saline, 100% serum, 100% blood, and 1.6-7.6 mg of iodine per milliliter of saline) with one imaging acquisition. Conclusion: Grating-based phase-contrast CT allows differentiation of simulated simple, protein-rich, hemorrhagic, and enhancing renal cysts in an in vitro phantom through simultaneous assessment of their distinct attenuation- and phase-contrast signal. © RSNA, 2014.
CRIS-Team Scopus Importer:2023-03-08